The Western canon : the books and school of the ages - Bloom, Harold (New York : Riverhead Books, 1995)
Includes criticism and interpretation of William Shakespeare, Dante, Cervantes, Montaigne, Moliere, John Milton, Samuel Johnson, Goethe, William Wordsworth, Jane Austen and Persuasion, Walt Whitman, Emily Dickinson, Charles Dickens and Bleak House, George Eliot and Middlemarch, Tolstoy, Ibsen, Freud, Proust, James Joyce and Ulysses, Virginia Woolf and Orlando, Franz Kafka, Jorge Luis Borges, Pablo Neruda, and Fernando Pessoa.
Preface and prelude -- I On the Canon -- Elegy for the Canon -- II The Aristocratic age -- Shakespeare, center of the Canon -- The Strangeness of Dante: Ulysses and Beatrice -- Chaucer: the Wife of Bath, the Pardoner, and Shakespearean character -- Cervantes: the play of the world -- Montaigne and Moliere: the Canonical elusiveness of the truth -- Milton's Satan and Shakespeare -- Dr. Samuel Johnson, the Canonical critic -- Goethe's Faust, Part Two: the countercanonical poem -- III The Democratic Age -- Canonical memory in the early Wordsworth and Jane Austen's Persuasion -- Walt Whitman as center of the American canon -- Emily Dickinson: blanks, transports and the dark -- The Canonical novel: Dicken's Bleak House, George Eliot's Middlemarch -- Tolstoy and heroism -- Ibsen: troll and Peer Gynt -- IV The Chaotic Age -- Freud: a Shakespearean reading -- Proust: the true persuasion of sexual jealousy -- Joyce Agon with Shakespeare -- Woolf's Orlando: feminism as the love of reading -- Kafka: Canonical patience and "indestructibility" -- Borges, Neruda, and Pessoa: Hispanic-Portuguese Whitman -- Beckett...Joyce...Proust...Shakespeare -- V Cataloging the Canon -- Elegiac conclusion -- Appendixes -- The Theocratic Age -- The Aristotic Age -- The Democratic Age -- The Chaotic Age: a conical prophecy -- Index.
Originally published: 1st edition New York : Harcourt Brace, c1994.
Includes index.
Keywords: Canon (Literature); Literature -- History and criticism